حماية العرض في الشريعة والقانون الجزائري - أبختي, السعيد (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2019)
تتناول هذه الرسالة موضوع حماية الشرف في الشريعة والقانون الجزائري دراسة مقارنة للوسائل والآليات. كما هي يبدأ من السؤال عن وسائل الثواب والعقاب في ذلك اتخذت الشريعة الإسلامية حماية لأعراض الناس؛ والآليات المنصوص عليها في القانون الجزائري لحماية شرفهم. وكذلك العثور على أوجه التشابه والاختلاف بين الشريعة والقانون في حماية الشرف؟ إن حماية العرض مقصد كبير في الإسلام، وحق تحددها القوانين الوضعية؛ بما في ذلك القوانين الجزائرية. هذا هو لارتباطها بالكرامة الإنسانية، وأمن و استقرار المجتمع. ولابد من معالجة هذا الموضوع، خاصة في عصرنا هذا الذي توفرت فيه الوسائل فالتواصل يختلف ويختلف، والكلمات ليس لها قيمة. ولذلك فإن هذه الرسالة تبحث في الوسائل التي يمكن بها للفكر الإسلامي الشريعة تحمي شرف الناس؛ سواء كان ذلك بالوسائل الوقائية كربط حفظ العرض بالإيمان، أو الوسائل الزجرية مثل العقوبة. ويسعى إلى الكشف عن الآليات والإجراءات التي تعتمدها القانون الجزائري درع لحماية الشرف؛ مع المقارنة بين الشريعة والقانون الجزائري لبيان أوجه التشابه والاختلاف. تتناول هذه الورقة الموضوع في ثلاثة فصول بعد مقدمة. وتناول الفصل الأول مفهوم الحماية الشرف في اللغة والشريعة والقانون. كما أنه يتناول العلاقة وبين حمايتها ومقاصد الشريعة والنظام العام. أما الفصل الثاني فقد أبرز وسائل تطبيق الشريعة الإسلامية يحمي الشرف؛ من خلال إظهار دور الإيمان والعبادة والأخلاق. أما الفصل الثالث فقد تناول آليات حماية الشرف في القانون الجزائري . ويتناول آليات الحماية لدى الجزائري الدستور من خلال منح الحرية وحقوق الإنسان والمعاقبة انتهاكها. ثم يبحث في آليات حماية الشرف في القانون الجنائي الجزائري من خلال التدابير الوقائية و الردعية ضربات الجزاء. أما خاتمة الأطروحة فقد تضمنت النتائج التي توصلت إليها الدراسة. كما يقدم توصيات تتضمن تقوية الدين وازع في النفس، والتركيز على ربط حماية العرض بال الإيمان والعبادة والأخلاق. This thesis examines the topic of honour protection in the Sharia and Algerian law, a comparative study of the means and mechanisms. As it starts from asking about the means of reward and punishment that Islamic law has taken to protect people's honour; and the mechanisms stipulated in the Algerian law to protect their honour. As well as finding the similarities and the differences between sharia and the law in the protection of honour? The protection of honour is a big aim in Islam, and a right established by the positive laws; including the Algerian laws. This is because of its connection with human dignity, and the security and stability of the society. This subject must be tackled, especially in our time when the means of communication vary and differ, and words have no value. Therefore, this thesis examines the means by which the Islamic sharia protects the honour of people; whether it is by preventive means such as linking the protection of honour with faith, or restraining means such as punishment. It seeks to unveil the mechanisms and procedures adopted by the Algerian law as a shield to protect honour; with a comparison between sharia and the Algerian law to show the similarities and the differences. This paper deals with the subject in three chapters after an introduction. In first chapter, it deals with the concept of protecting honour in language, sharia, and law. Also, it deals with the relation between protecting it and the aims of Sharia and public order. The second chapter highlights the means by which the Islamic sharia protects honour; through showing the role of faith, worship, and morals. The third chapter deals with the mechanisms of protecting honour in the Algerian law. It tackles the protective mechanisms of the Algerian constitution through granting freedom and human rights, and punishing its violation. Then, it examines the mechanisms of protecting honour in the Algerian penal code through protective measures and Deterrent penalties. The conclusion of the thesis contains the findings of the study. It also gives recommendations that include the strengthening of religious scruples in the soul, and focusing on linking the protection of honour with faith, worship, and morality.
دراسة مقارنة في الوسائل و الأليات
أطروحة دكتوراه تخصص التفسيير و التشريع المقارن في العلوم الإسلامية
Keywords: الكلمات المفتاحية: الحماية، الشرف، الشريعة، القانون الجزائري، الوسائل، الآليات.; Keywords: protection, honour, sharia, Algerian law, means, mechanisms.